Income shocks and mental health: evidence from oil royalties - Castro, Caio de Souza (2020)
This dissertation examines how revenue shocks in Brazilian municipalities affect the mental health of their population. We exploit a plausible exogeneity regarding oil royalties distribution to establish a causal relationship between resource windfalls and the number of occurrences of mental illness. Using within municipality variation in oil revenues, we find that receiving more oil royalties reduces both hospitalizations due to cirrhosis and ambulatory procedures related to mental health. Our results are robust to a series of exercises. Our findings suggest that one possible explanation for this is that royalties have a positive impact on local economic outcomes which is consistent with findings from the literature.